Associations of family and social contact with health among Italian grandparents - Cecilia Tomassini; Jessica Zamberletti; Carlo Lallo; Giulia Cavrini (Genus, 2020)
Abstract Past research has documented the positive influence of frequent interactions with social networks on several health outcomes in later life, with different patterns by gender. In this study, we explore the association of frequent contact with different members of the social network (namely partner, grandchildren, siblings, friends and neighbours) on self-perceived health status and the limitation of illnesses among older grandparents in Italy, using a large national representative survey. Our results confirm the positive association between good health indicators and frequent contact with members of the “horizontal” network (partner, siblings and friends), while a more ambiguous association has been found with frequent face-to-face contact with children and grandchildren. The results hold for both male and female grandparents. The Mediterranean family-focused culture may possibly explain the distinctly Italian results.